Ultrasonographic characteristics of benign mammary lesions in bitches - Gasser, B. [UNESP]; Rodriguez, M. G. K. [UNESP]; Uscategui, R. A. R. [UNESP]; Silva, P. A. [UNESP]; Maronezi, M. C. [UNESP]; Pavan, L. [UNESP]; Feliciano, M. A. R. [UNESP]; Vicente, W. R. R. [UNESP] (Czech Academy Agricultural Sciences, 2018)
The aim of this study was to evaluate the applicability of B-mode, Doppler, acoustic radiation force impulse elastography and contrast-enhanced ultrasound exams in the differentiation of neoplastic and non-neoplastic benign mammary lesions in bitches. This research was conducted as a prospective secondary observational cohort (2014-2016) study, which included 36 mammary lesions, evaluated physically and by ultrasound (B-mode, Doppler, contrast-enhanced ultrasound and acoustic radiation force impulse) exams prior to mastectomy and histopathological classification as neoplastic or non-neoplastic lesions. All ultrasonographic parameters studied were compared between histopathological classifications using Fisher's or Student's tests and differences were considered significant when P < 0.05. Out of 36 benign mammary lesions evaluated, 25 were classified as neoplastic and 11 as non-neoplastic. The qualitative and quantitative parameters evaluated using the different ultrasound methods were not effective (P > 0.05) in differentiating between neoplastic and non-neoplastic mammary masses in bitches. Nevertheless, some B-mode variables, such as longitudinal length (P = 0.0292), width/length ratio (P = 0.0001) and width/height ratio (P = 0.0001) showed limited efficacy in the differentiation of mammary lesions types. In conclusion, ultrasonographic evaluation of benign canine mammary lesions did not allow differentiation between neoplastic and non-neoplastic tissues and only a few B-mode variables may aid in the prediction of specific tumour types.
Keywords: Doppler; acoustic radiation force impulse; ARFI elastography; contrast-enhanced ultrasound; dogs; neoplastic